Improving Understanding of Faith in the Apostles Material Through the Discovery Learning Method at SMP Negeri 2 Teluk Mengkudu - Suheri; Jusmaita (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve the understanding of the material on faith in the apostles in grade VIII students of SMP Negeri 2 Teluk Mengkudu through the application of the Discovery Learning method. The material on faith in the apostles has an important role in the formation of students' character and faith, but students' understanding of this material is often still low. The Discovery Learning method was chosen because it can increase student involvement in the learning process, encourage them to find knowledge independently, and develop critical thinking skills. This study used a quasi-experimental method with a pre-test and post-test research design. A total of 30 grade VIII students who were the samples of this study were divided into two groups, namely the experimental group who were given treatment using the Discovery Learning method and the control group who used conventional learning methods. Data were obtained through tests to measure student understanding before and after learning, as well as observations to see student activities during the learning process. The results of the study showed a significant increase in the understanding of the material on faith in the apostles in the experimental group after the application of the Discovery Learning method. Thus, the application of this method can be an effective alternative in improving students' understanding of the material on faith in the apostles, and can be applied to learning in Islamic Religious Education subjects in schools.